Comparative performance of pxts versus creosote in an awpa e7 field stake test - D. Nicholas, Darrel; Rowlen, Amy; Milsted, David (Maderas. Ciencia y Tecnología, 2021)
A need exists to develop new organic, environmentally benign wood preservatives for industrial applications to replace the older creosote and pentachlorophenol systems. In this study the performance of creosote at three retentions was compared to a new wood preservative candidate formulated with Polymeric Xylenol Tetrasulfide (PXTS) in an E7 AWPA field study using two sets of southern pine and yellow poplar field stakes treated with three creosote retentions or five retentions of PXTS. The stakes were installed at two test sites and evaluated after 3,5 years, 6 years, and 14 years exposure. After six years of exposure at both sites, which is double the minimum recommended exposure period of three years’ field data for AWPA submission of a proposed new preservative system, the average decay ratings data for southern pine stakes after three years exposure was not sufficient to definitively determine which system provides superior protection against decay and termite attack (Creosote at the AWPA UC4B pole retentions versus pine stakes treated with much lower PXTS levels). However, after a longer exposure time of 14 years the data conclusively shows that pine stakes treated to the utility pole AWPA UC4B creosote retention performed poorer at both sites against decay and termite degradation than pine stakes treated with 26 Kg/m3 PXTS. Similar results were obtained with the yellow poplar stakes. We conclude that: 1) much longer E7 exposure times are necessary then the minimum recommended three years in the AWPA GDA Standard for submission of new systems to definitively determine the efficacy of a proposed oil borne system compared to the efficacy of a traditional organic preservative for commercial applications, and 2) long term field PXTS performance against decay and termite deterioration is equal or greater than that obtained with creosote at about four times the PXTS retention.